Chemistry Modelling and Simulation through Agent Oriented Modelling and Netlogo - Cheah, Wai Shiang; Shane, Nissom; Sim, Siong Fong; Muhammad Asyraf, Khairuddin (Universiti Teknikal Malaysia (UTEM), 2017)
—Education technology is used to enhance students’ understanding on science subject. Within the Faculty of Resource Science and Technology (FRST) at Universiti Malaysia Sarawak (UNIMAS) students face difficulty to visualize on the composition of atoms or molecule due to complexity of the topics. Although, students can attend Chemistry labs, the usage of labs are insufficient due to lack of instruments and lab materials. Hence, it is always a challenge to deliver some Chemistry topics and students always feel difficulty on understanding some Chemistry subjects. We believe that simulation can fill this gap. However, how to model the Chemistry theory and develop the Chemistry simulation model is challenging. This paper introduces an Agent Oriented Modelling(AOM) and Netlogo for chemistry modelling and simulation. The AOM is investigated in Chemistry domain and the potential usage is reported. From the finding, the AOM can help the modeller to understand the Chemistry theory and conceptualize the Chemistry theory into agent model and simulation. On the other hand, the agent model (e.g. domain model) has enabling the communication between researchers from two disciplines. Although we have successful model the Chemistry theory, how the simulation can support the Chemistry learning will be explored in the coming periods.